Right now versus back then: Recency and remoteness as discursive resources in online reviews. (September 2015) - Vásquez, Camilla
Abstract: This study explores variation in temporal reference within a dataset of 1000 user-generated online consumer reviews, sampled from 5 different websites. Analyzing the proportion of references to recency compared with references to remoteness in these texts, an overall trend toward remoteness was found, which diverges from earlier findings about temporality in other types of social media, such as Facebook and Twitter . Further considering specific examples from three of the five review sites ( Yelp, Amazon, and Epicurious ), this paper offers insights into how both the remote past and the present are variably deployed as discursive resources by the authors of these online texts. In addition, the study׳s findings reveal that whereas lexical resources are used to refer to the present/recent past, references to the remote past rely much more on grammatical resources. Consequently, in order to provide a more complete account of time reference, I argue that it is important to consider a broader range of linguistic features (e.g., grammatical aspect, prepositional phrases) rather than concentrating exclusively on temporal adverbs when making claims about temporality in social media.